PERAN BPKH TERHADAP PENGEMBANGAN PASAR MODAL SYARIAH DALAM UU NOMOR 34 TAHUN 2014 TENTANG PENGELOLAAN KEUANGAN HAJI - Ahmad Fauzi (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Law Number 34/2014 concerning Hajj Financial Management, mandates to establish a special hajj financial management body (Hajj Fund Management Agency, BPKH) tasked with managing the revenue, development, expenditure, and accountability of Hajj finance. BPKH has the authority to manage hajj funds around IDR 115 trillion as of April 2019. BPKH must place these funds into sharia investment instruments, taking into account safety, prudence, value of benefits and liquidity. According to Government Regulation Number 5/2018 (PP No. 5/2018), a minimum of 15% of the pilgrimage funds will be placed on the Islamic capital market. The form can be State Sharia Securities, Bank Indonesia Sharia Certificates, sharia shares, sukuk, mutual funds and various other sharia securities recognized by the Financial Services Authority (OJK). BPKH's investment in the Islamic Capital Market will gradually increase to 35% in 2021 with the amount estimated to reach IDR 47.35 trillion. The strong role of the increasing Islamic Capital Market in forming market capitalization (the Composite Stock Price Index, IHSG) indicates that the Islamic Capital Market has a large role in driving economic growth in Indonesia. So BPKH investment has a strategic position in the effort to develop the Islamic Capital Market in Indonesia.